ANALISIS KOMPARATIF ETIKA PROFESI GURU PERSPEKTIF AL-GHOZALI DAN HASYIM ASY’ARI - Muslim, Ahmad Buchori; Maliha, Hilya (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
The declining quality of education and the moral crisis among both teachers and students have become pressing issues in today’s educational landscape. One of the main causes of this crisis is the erosion of ethics, which should serve as the foundation of values and norms guiding educational practice. This study aims to explain and analyze professional teaching ethics from the perspectives of two prominent scholars: Al-Imam Al-Ghazali in Ihya Ulumuddin and KH. M. Hasyim Asy’ari in Adab al-‘Alim wa al-Muta’allim. The research employs a qualitative descriptive approach with a library research method. Data collection was conducted through an in-depth review of primary books, journals, and other relevant literature, and the data were analyzed using content analysis. The findings reveal that, according to Al-Ghazali, a teacher must show compassion toward students, emulate the Prophet Muhammad’s character, and teach sincerely for the sake of Allah’s pleasure. Students, in turn, are expected to purify their souls from negative traits and seek knowledge solely for the sake of Allah. Meanwhile, Hasyim Asy’ari views the teaching profession as deeply spiritual and sacred, requiring teachers to uphold high professional responsibility toward themselves, their students, and ultimately, to God. This ethical foundation is essential to restoring moral integrity in Islamic education